AN ANALYSIS OF TERM SARIYYAH IN THE TRANSLATION OF THE BOOK TITLED NURUL YAQIN FI SIRAH SAYYIDIL MURSALIN (2010) BY SHEIKH MUHAMMAD AL-KHUDHARIY - Syahrefi, Namira Fauzia; Muta'ali, Abdul (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2021)
This paper presents the analysis of the translation of the term sariyyah in the book